cGAS-agonistic spherical nucleic acids reprogram the glioblastoma immune microenvironment and promote antitumor immunity - Akanksha S. Mahajan; Corey Dussold; Seunghyun Kim; Rachel Jarvis; Lisa A. Hurley; Serena Tommasini-Ghelfi; Jungsoo Park; Connor M. Forsyth; Bin Zhang; Jason Miska; Amy B. Heimberger; Chad A. Mirkin; et al. (Proceedings of the National Academy of Sciences, 2025)
The cyclic GMP-AMP synthase-Stimulator of Interferon Genes (cGAS–STING) pathway is an important DNA-sensing mechanism that increases T cell trafficking and activation in tumors and reverses the immunosuppressive phenotype of myeloid cells. Therefore, direct STING targeting using synthetic cyclic dinucleotides (CDNs) is an attractive strategy for treating lymphocyte-depleted and myeloid cell–enriched tumors, such as glioblastoma (GBM). However, inadequate bioavailability and poor cellular accumulation limit the clinical development of CDNs, particularly for noninvasive administration strategies. Spherical nucleic acids (SNAs) have emerged as promising modular constructs for creating therapeutic lead compounds for many diseases, including different forms of cancer. Here, we report the development of cGAS-activating SNAs that consist of gold nanoparticle cores functionalized with a shell of densely packed interferon-stimulatory DNA oligonucleotides (ISD 45 -SNAs). These nanostructures bind to cGAS, the sensor of cytosolic dsDNA upstream of STING, promoting the catalytic production of endogenous CDNs and downstream STING activation more potently than clinically tested CDNs. When administered intranasally or intratumorally to poorly immunogenic syngeneic GBM mouse models, ISD 45 -SNAs inhibit tumor growth more effectively than CDNs and promote long-term animal subject survival through specific cGAS–STING pathway activation. ISD 45 -SNAs induce a proinflammatory immune microenvironment enriched with effector T cells and proinflammatory macrophages. When coadministered with immune checkpoint inhibitors (ICI), they abolish GBM tumor development and induce long-term antiglioma immunity. These studies establish ISD 45 -SNAs as an immune-stimulatory modality for triggering innate and adaptive immune responses and increasing ICI efficacy for GBM treatment.